Formalization of operational management and its impact on the innovativeness of IT companies from Lubuskie Voivodeship - Inków Monika (Management)
In the changing environment, innovation gives organizations a chance to survive and develop. Researchers indicate that successfully implemented innovations are a source of competitive advantage for an organization. In source literature we can find examples of various tools recommended by the authors that increase the probability of innovation success. As some researchers note, the role of these tools has been questioned, which is related to the impact of formalization on innovation. In recent years, researchers have focused their efforts on determining whether formalization improves or deteriorates innovation; however, when analyzing the literature, it can be noticed that the number of studies on innovation and its determinants is significant, while the number of publications on the impact of formalization on organizational innovation is low. In addition, it can be noted that so far, researchers have not come to a consensus regarding the impact of formalization on either organizational results or innovation; therefore, the assumption of the presented work is to fill this gap to some extent. The aim of this article is to present the preliminary results of a broader research project on the relationship between the formalization of operational management and the innovation of IT organizations in Lubuskie Voivodeship.